"When Freedom is Close": Jürgen Moltmann's Use of Contradiction in his Trilogy - Best, Daniel S. (My University, 2015)
Jürgen Moltmann's trilogy-Theology of Hope, The Crucified God, and The Church in the Power of the Spirit-is pervaded by the concept of "contradiction." Secondary literature commonly alludes to his theology of contradiction, describing his theology as "dialectical," but the literature rarely analyzes it comprehensively. This thesis seeks to fill this lack. It argues that in Moltmann's trilogy God creates and fosters in the world three different types of contradiction (objective, subjective and active) through three different means (God's promises, his crucifixion, and the work of his Spirit in and through the Church) in order to accomplish his purposes. The inductive sections of the thesis show that contradiction exists in nearly every chapter of each book. The systematic sections show contradiction is central to the main systematic theological topics of the trilogy. Understanding Moltmann's theology of contradiction this way allows for clearer interpretation of his theology as a whole.
Keywords: freedom, contradiction, trilogy, Jürgen Moltmann, God, spirit, theology